"A Woman's Degree Must End in the Kitchen": Expectations of Women in the Eastern Democratic Republic of Congo. (May 2022) - Mulumeoderhwa, Maroyi
This study draws on a qualitative approach to explore how adolescents perceive women's and men's roles in marriage and family life. A sample of 56 boys and girls aged 16–20 from two urban and two rural high schools in South Kivu province took part in focus groups, and 40 of them were subsequently interviewed individually. The results show that most male participants believe husbands should fill the breadwinner role, and expect wives to remain the primary caretakers. Female participants reported that men are reluctant to allow their wives to have a job despite their degrees. However, most female participants disapproved of the mentioned beliefs of expecting wives to remain home doing housework and the husband to be the only primary breadwinner. The majority of male and female participants identified socio-cultural pressure for men (rather than women) to acquire education, formal employment, and, eventually, household decision-making. There is a need to challenge the structures of rigid gender roles that relegate women to a secondary role in work, making them "naturally" responsible for domestic chores and childcare.